Optimizing the Plant Population and Time of White Lupine Intercropping with Food Barley in Northwest Ethiopian Highlands - Getahun, Sewnet; Alemayehu, Getachew; Mulatu, Kassaye (Journal of Agriculture and Environmental Sciences, 2021)
Lupine has traditionally been intercropped with food barley in northwest Ethiopian highlands. But, thereis no any documented information about the optimum plant population and time of white lupine intercropping withfood barley in these areas. Hence, a field experiment was conducted on plant population and time of lupineintercropping with food barley in 2017 and 2018 main cropping season in Gozamin highland, northwest Ethiopia, todetermine the optimum plant population and time of lupine intercropping for maximum productivity of food barleyfields. Factorial combinations of three plant population (500000, 250000 and 166667 plants/ha) and four time oflupine additive series intercropping (simultaneously, two weeks, four weeks and six weeks after barley sowing) withfood barley were laid out in randomized compete block design with three replications. Sole food barely and solelupine were included as a comparison purpose. The results indicated that there was no significant difference amongtreatment combinations for biomass and grain yields of food barley. However, highly significant differences amongtreatment combinations were observed for biomass and grain yields of lupine. The highest land equivalent ratio(1.48), relative economic efficiency (42.61%), and net economic return (Birr 38,160/ha) with acceptable highermarginal rate of return (598.68%) were recorded in the combination of 166667 plants/ha plant population andsimultaneous time of lupine additive intercropping with food barley.